The kill list - Forsyth, Frederick, 1938- (G.P. Putnam's Sons, 2013)
When a terrorist known as the Preacher targets for assassination a retired Marine general, whose son is TOSA's top hunter of men, the terrorist becomes the hunted -- landing him at the top of TOSA's Kill List.